Effects of testosterone on the transgender male voice. (19th September 2016) - Irwig, M. S.; Childs, K.; Hancock, A. B.
Summary: There is sparse prospective data on the effects of testosterone therapy on the voices of transgender men (also referred to as trans men or female‐to‐male transsexuals). Our aim was to investigate the timing and degree of voice deepening over 12 months among an ethnically diverse sample of transgender men. This was a prospective 12‐month study at an academic outpatient endocrinology clinic and speech and voice center. The participants were seven transgender men naïve to testosterone therapy. All patients received two voice assessments at baseline and one assessment at 3, 6, 9, and 12 months while on intramuscular testosterone esters. Serum testosterone and estradiol concentrations were measured at baseline and every 3 months. All seven transgender men reached a cisgender male mean fundamental frequency (MF0) within 6 months of testosterone therapy and four continued to experience a decrease after 6 months. The mean decrease in MF0 after 12 months of testosterone therapy was 6.4 semitones (49 Hz). Several patterns emerged regarding the extent and timing. For example, some participants showed no decrease in MF0 within the first 3 months of testosterone therapy, whereas others showed their greatest decrease in MF0. We concluded that transgender men who start testosterone therapy display different patterns of voice lowering. Clinicians should counsel transgender men that they may or may not experience voice lowering within the first 3 months of testosterone therapy and that the majority of voice deepening will occur within 6–9 months.